ABCC6–Mediated ATP Secretion by the Liver Is the Main Source of the Mineralization Inhibitor Inorganic Pyrophosphate in the Systemic Circulation—Brief Report - Jansen, Robert S. (Arterioscler Thromb Vasc Biol, 2014)
OBJECTIVE—: Mutations in ABCC6 underlie the ectopic mineralization disorder pseudoxanthoma elasticum (PXE) and some forms of generalized arterial calcification of infancy, both of which affect the cardiovascular system. Using cultured cells, we recently showed that ATP-binding cassette subfamily C member 6 (ABCC6) mediates the cellular release of ATP, which is extracellularly rapidly converted into AMP and the mineralization inhibitor inorganic pyrophosphate (PP(i)). The current study was performed to determine which tissues release ATP in an ABCC6-dependent manner in vivo, where released ATP is converted into AMP and PP(i), and whether human PXE ptients have low plasma PP(i) concentrations. APPROACH AND RESULTS—: Using cultured primary hepatocytes and in vivo liver perfusion experiments, we found that ABCC6 mediates the direct, sinusoidal, release of ATP from the liver. Outside hepatocytes, but still within the liver vasculature, released ATP is converted into AMP and PP(i). The absence of functional ABCC6 in patients with PXE leads to strongly reduced plasma PP(i) concentrations. CONCLUSIONS—: Hepatic ABCC6-mediated ATP release is the main source of circulating PR, revealing an unanticipated role of the liver in systemic PP(i) homeostasis. Patients with PXE have a strongly reduced plasma PP(i) level, explaining their mineralization disorder. Our results indicate that systemic PP(i) is relatively stable and that PXE, generalized arterial calcification of infancy, and other ectopic mineralization disorders could be treated with PP(i) supplementation therapy.